Anti-corrosion and waterproof sealant for nuts, preparation method and application of anti-corrosion and waterproof sealant
By using nut anti-corrosion and waterproof sealants prepared by polyisobutene and other materials, the existing sealants may release harmful substances and insufficient curing time during long-term use, achieving environmentally friendly, convenient use and good sealing effect.
Patent Information
- Application Number
- CN202510042573.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
Existing sealants may release harmful substances during long-term use, affecting the environment and human health. At the same time, their curing time is insufficient or too long, affecting the sealing effect and construction efficiency.
A nut anti-corrosion waterproof sealant is prepared by using polyisobutylene, thermoplastic elastomer, softener, tackifier, filler aggregate, and a mixture of modified aluminum tripolyphosphate and zinc oxide as anti-rust preservatives. The sealant is easy to transport and use without waiting for curing, and has good corrosion resistance and waterproof properties.
It realizes environmentally friendly sealant without waiting for curing, has good corrosion and waterproof performance, reduces transportation costs and improves construction efficiency.
Smart Images

Figure CN119823714A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of sealants, and in particular to a nut anti-corrosion and waterproof sealant, a preparation method and application thereof. Background Art
[0002] As a widely used fastener, the sealing performance of nuts is directly related to the safety and reliability of the entire structure. Traditional self-clinching nuts cannot meet the requirements of waterproof and dustproof when they do not have sealing performance. Although measures such as coating with glue or adding sealing structures can improve the sealing performance, they may affect the riveting performance and safety factor of the nuts. Therefore, the use of sealants is of great significance to improve the sealing performance of nuts and ensure the long-term stable operation of the structure.
[0003] Although fluorine-containing sealants have good sealing properties, their decomposition products may cause environmental pollution. Fluoride emissions pose potential risks to the environment and human health. Therefore, with the increasing awareness of environmental protection, it is particularly important to develop and use environmentally friendly sealants. Traditional fluorine-containing sealants may release fluoride during long-term use, causing pollution to soil and water sources. Therefore, finding and developing fluorine-free or low-fluorine environmentally friendly sealants is the trend of industry development.
[0004] The curing time of the sealant has a direct impact on its bonding performance and sealing effect. Insufficient curing time may lead to insufficient bonding between the sealant and the sealed material, which cannot withstand the expected load or environmental stress, and is prone to failure phenomena such as peeling and cracking. In addition, insufficient curing time may also affect the interface sealing between the sealant and the sealed material, reducing the overall sealing effect. In some urgent or fast-construction projects, too long curing time will delay the progress of subsequent projects and affect construction efficiency. Therefore, reasonable control of the curing time of the sealant is crucial to ensure its good bonding performance and sealing effect, as well as to improve construction efficiency. Summary of the invention
[0005] The purpose of the present application is to provide a sealant with good anti-corrosion and waterproof properties.
[0006] Another object of the present application is to provide a seal that is easy to use, has low transportation costs, and does not require waiting for curing.
[0007] In order to achieve the above objectives, the technical solution adopted in this application is: to provide a nut anti-corrosion and waterproof sealant, the preparation raw materials include the following components: polyisobutylene, thermoplastic elastomer, softener, tackifier, filling aggregate and anti-rust and corrosion inhibitor, and the anti-rust and corrosion inhibitor is a mixture of modified aluminum tripolyphosphate and zinc oxide.
[0008] As a preference, the modified aluminum tripolyphosphate and the zinc oxide are mixed in a mass ratio of (2.5-1):1 to obtain the rust and corrosion inhibitor.
[0009] As a preference, the modified aluminum tripolyphosphate and the zinc oxide are mixed in a mass ratio of 1:1 to obtain the rust and corrosion inhibitor.
[0010] As a preference, the amount of the anti-rust and anti-corrosion agent added is 3% to 7% of the total mass.
[0011] As a preferred embodiment, the preparation raw materials also include filling aggregates, and the preparation raw materials include the following components: 20 to 60 parts by mass of the polyisobutylene, 10 to 40 parts by mass of the softener, 10 to 20 parts by mass of the thermoplastic elastomer, 50 to 80 parts by mass of the tackifier, and 60 to 100 parts by mass of the filling aggregates, and the amount of the rust preventer and corrosion inhibitor is 3% to 7% of the total mass.
[0012] As a preferred embodiment, the raw materials for preparation include the following components: 40 parts by mass of the polyisobutylene, 25 parts by mass of the softener, 10 parts by mass of the thermoplastic elastomer, 70 parts by mass of the tackifier, 85 parts by mass of the filling aggregate, and the amount of the rust and corrosion inhibitor is 3% of the total mass.
[0013] As another preferred embodiment, the filling aggregate is nano calcium carbonate and / or ultrafine wollastonite powder, the tackifier is a combination of any one or more of 138 resin, terpene resin, carbon nine or carbon five, the softener is cycloalkane, and the thermoplastic elastomer is a mixture of modified linear thermoplastic styrene butadiene rubber SEBS and linear SEPS.
[0014] More preferably, the Mooney viscosity ranges from 3 to 4.
[0015] The present application also provides a method for preparing the above-mentioned anti-corrosion and waterproof sealant for nuts, which comprises heating the reaction container, adding the polyisobutylene and the softener at the same time, and continuously stirring until dissolved. After heating the reaction container to 100-120° C., the thermoplastic elastomer, the anti-corrosion and rust inhibitor, and the adhesive are added in sequence, and the next reactant is added after each of the above-mentioned reactants is dissolved. Finally, the reaction container is heated to 130-150° C. and a tackifier is added. After the tackifier is dissolved, the filling aggregate is added to obtain the anti-corrosion and waterproof sealant for nuts.
[0016] The present application also provides a seal, comprising an open shell, wherein the shell contains any of the above-mentioned nut anti-corrosion and waterproof sealants, or the nut anti-corrosion and waterproof sealants prepared by the above-mentioned preparation method.
[0017] Compared with the prior art, the beneficial effects of this application are:
[0018] (1) The nut anti-corrosion and waterproof sealant of the present application is relatively environmentally friendly and will not release substances that are harmful to the environment during long-term use, which is beneficial to protecting the environment;
[0019] (2) The nut anti-corrosion and waterproof sealant of the present application has good anti-corrosion and waterproof intrusion effects, and the sealant of the present application is in a semi-solidified state, which is suitable for transportation and reduces the curing time;
[0020] (3) The preparation method of the nut anti-corrosion and waterproof sealant of the present application is simple and easy to operate, and the reaction raw materials and reaction equipment are easy to obtain
[0021] (4) The seal of the present application is easy to use, has low transportation cost, and has good anti-corrosion effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Photo of the nut anti-corrosion and waterproof sealant for this application;
[0023] Figure 2 Another angle photo of the nut anti-corrosion and waterproof sealant for this application. DETAILED DESCRIPTION
[0024] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0025] The terms "including" and "having" and any variations thereof in the specification and claims of the present application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.
[0026] The present application provides an anti-corrosion and waterproof sealant for nuts, comprising the following components: 20 to 60 parts by mass of polyisobutylene, 10 to 40 parts by mass of a softener, 10 to 20 parts by mass of a thermoplastic elastomer, 50 to 80 parts by mass of a tackifier, 60 to 100 parts by mass of a filling aggregate, and an anti-rust and anti-corrosion agent, wherein the amount of the anti-rust and anti-corrosion agent used is 3% to 7% of the total mass of the sealant.
[0027] Polyisobutylene (PIB) is a polymer material with many excellent properties. It is a colorless, odorless, non-toxic viscous or semi-solid substance with good resistance to heat, oxygen, ozone, weather, UV, acid and alkali. It is a nearly fully saturated hydrocarbon elastomer, so it cannot be cured with ordinary sulfur curing system, and usually uses peroxide curing system.
[0028] Polyisobutylene has a wide range of applications, which is closely related to its molecular weight. Low molecular weight polyisobutylene and medium molecular weight polyisobutylene can be used as oil additives, adhesives, sealants, coatings, lubricants, plasticizers and cable impregnation agents. High molecular weight polyisobutylene can be used as impact modifier additives for plastics, raw rubber and thermoplastic elastomers. In addition, polyisobutylene has very important uses in lubricant additives, polymer material post-processing, medicine and cosmetics, food additives and other fields.
[0029] The application of polyisobutylene in sealants is mainly reflected in its excellent atmospheric, aging and weather resistance, as well as its impermeability to water vapor, which makes it very suitable for the production of various sealants and insulating glass sealants. The addition of polyisobutylene can increase the flexibility and permeability of the product, improve the adhesion and elasticity of the sealant, thereby maintaining the sealing effect for a long time and preventing the intrusion of water vapor and dust. In addition, polyisobutylene-filled sealant formulas can increase viscosity and weather resistance, improve water resistance and oxidation stability, and are used as raw polymers for window sealants due to their excellent barrier properties and low-temperature elasticity. Sealing tapes containing polyisobutylene can prevent corrosion of pipes in underground or underwater environments and provide a long-lasting sealing effect.
[0030] In some embodiments, the polyisobutylene is preferably PB050 and / or PB1300 of Dalin, South Korea. PB050 of Dalin, South Korea is a low molecular weight polyisobutylene. PB050 has high adhesion, oxidation resistance, heat resistance and chemical stability, and is therefore widely used in many industrial fields. Since it is non-toxic and tasteless, and no chemical additives are used in the production process, PB050 is also a green and environmentally friendly chemical raw material, commonly used as a raw material in the fields of hot melt adhesives, adhesives, sealants, coatings, inks, etc.
[0031] Dalin PB1300 is a relatively high molecular weight polyisobutylene with an average molecular weight of about 1300. It is a colorless to light yellow viscous liquid or elastic rubber-like semisolid with excellent chemical stability and is not easily oxidized by sunlight and high temperature. PB1300 has excellent solubility and compatibility, and can be well dissolved in aliphatic and aromatic solvents, and has good compatibility with a variety of organic substances such as wax, rosin, asphalt and gum. In addition, PB1300 also has excellent antioxidant and UV resistance, and can maintain its original physical and chemical properties in long-term light and oxidation environments. It is widely used in fuel and lubricant additives, adhesives, waterproof materials, electrical insulation materials and other fields.
[0032] In certain embodiments, the softener of the present application is cycloalkane. It is a petroleum fraction with cycloalkane as the main component, with the characteristics of saturated cyclic carbon chain structure and low pour point, high density, high viscosity, no toxic side effects. Cycloalkane oil is mainly used as a softener and operating oil in the rubber industry, which can improve the processing performance and use performance of rubber, increase the plasticity of rubber, reduce the viscosity of rubber, improve dispersibility and miscibility, and improve the tensile strength, elongation and wear resistance of vulcanized rubber. Cycloalkane oil is widely used in the processing of rubber products such as SBS (thermoplastic elastomer), NR (natural rubber), SBR (styrene-butadiene rubber), BR (cis-butadiene rubber) and EPM (ethylene-propylene rubber), EPDM (ethylene-propylene-diene rubber). It is suitable for the production of daily life, the ideal rubber oil of hygienic rubber, and is also the filling oil of rubber synthesis and the operating oil or softener of rubber product processing.
[0033] As a softener, naphthenic oil can reduce the consumption of mixing power, promote the uniform dispersion of various auxiliary materials, and improve the process properties of vulcanized rubber such as elongation and resilience. Naphthenic oil acts as a lubricant in rubber, weakening the intermolecular force of rubber hydrocarbons, increasing the sliding between molecular chains, and making molecular movement easier. Due to its unique chemical structure and physical properties, cycloalkane softeners play an important role in rubber processing. They can not only improve the processing performance of rubber, but also enhance the physical properties of rubber products.
[0034] In certain embodiments, the softener cycloalkane can be a cycloalkane rubber oil KN series product of Karamay Petrochemical, such as KN4006 and / or KN4010. The cycloalkane rubber oil KN4006 of Karamay Petrochemical is a high-grade cycloalkane rubber oil, which is produced by the vacuum distillate oil of Xinjiang Karamay low-condensable thick oil or propane deasphalted oil through a high-pressure hydrogenation process. This product is famous for its water white color, harmless, no side effects and no potential risk of causing disease. It has the characteristics of low condensation point (pour point), low aromatics, and high cycloalkane content, and is an ideal environmentally friendly cycloalkane rubber processing oil for the rubber industry. KN4006 is particularly suitable for use as a filling oil in the synthetic rubber industry, such as thermoplastic cold elastomer SBS, styrene-butadiene rubber SBR, or as an operating oil in the rubber processing industry, such as TPR granules or other shoe materials in the shoemaking industry, and is particularly suitable for rubber products with strict color requirements.
[0035] Karamay Petrochemical's naphthenic rubber oil KN4010 is another product in the KN series. It is also produced using Xinjiang low-condensing naphthenic fraction and advanced three-stage high-pressure hydrogenation technology. It has excellent appearance color, high naphthenic content and low volatility loss. KN4010 has excellent performance in terms of resistance to sunlight and thermal oxidation, and is an environmentally friendly, pollution-free, high-quality naphthenic rubber oil. This rubber oil is widely used in the production of high-end shoe materials and adhesives with SBS as the main raw material, and is also widely used in the processing of rubber products such as NR, SBR, BR and EPM. It is an ideal rubber oil for the production of high-end daily life and sanitary rubber.
[0036] Thermoplastic elastomers have excellent waterproof and weather resistance and are used to manufacture waterproof membranes, waterproof coatings and other products. These products are required to have excellent waterproof and weather resistance to ensure the waterproof effect of buildings under severe weather conditions. TPE waterproof materials have been widely used in the field of building waterproofing due to their unique performance advantages, and have effectively improved the waterproof performance and durability of buildings. In addition, TPE sealing strips are increasingly prominent in modern life due to their importance in aesthetics, environmental protection and comfort functions, especially in doors and windows, furniture, automobiles, household appliances, etc. TPE sealing strips have both the high elasticity of elastomers and the excellent properties of plastics, a wide range of hardness, and are environmentally friendly. They are easy to process and can be recycled and reused, so they are very popular in many fields.
[0037] In some embodiments, the thermoplastic elastomer of the present application includes a mixture of modified linear thermoplastic styrene butadiene rubber SEBS and linear SEPS. In some preferred embodiments, the addition amount of SEBS and SEPS is 1:1.
[0038] SEBS does not contain active carbon-carbon double bonds, so it has excellent tolerance to ozone, ultraviolet rays, and heat; it has good temperature resistance, low brittle temperature (≤-60°C), maximum operating temperature of up to 149°C, and decomposition temperature of more than 270°C in an oxygen atmosphere; it can be dissolved in many common solvents, blended with a variety of polymers, and can be filled with oils commonly used in the rubber industry; it is an elastomer that can be used without vulcanization, and its processing performance is similar to that of SBS, and the scraps can be reused, meeting environmental protection requirements;
[0039] SEPS (hydrogenated styrene-isoprene thermoplastic elastomer) is a high-performance polymer material made from styrene-isoprene-styrene block copolymer (SIS) through selective hydrogenation reaction. SEPS has excellent weather resistance, acid and alkali resistance and wear resistance, which makes it widely used in many fields.
[0040] The main function of the tackifier in the sealant is to increase the viscosity and adhesion of the colloid, ensure a strong bond between the sealant and the sealed material, and at the same time improve the rheological properties of the colloid, enhance its stability and durability in different environments, thereby ensuring the long-term effectiveness and reliability of the sealant.
[0041] Tackifiers indirectly affect the cure time of sealants by changing their chemical composition and physical properties. They may affect the speed of the curing reaction, interact with environmental factors such as temperature and humidity, and interact with other components of the sealant to adjust the flow and adhesion of the sealant, thereby affecting the curing process. Therefore, the addition of tackifiers can optimize the curing characteristics of the sealant to meet specific application requirements without changing its basic properties.
[0042] In some embodiments, the tackifier includes 138 resin, terpene resin, carbon nine, and carbon five.
[0043] 138 resin, also known as rosin resin 138, is a natural polymer compound, mainly extracted from the resin secreted by pine trees. It has good heat resistance, adhesion and corrosion resistance, and is a green and environmentally friendly natural polymer material. 138 resin has a high softening point of 85-95°C, light color, low acid value, good solubility and compatibility, can be dissolved in a variety of solvents, and can be mixed with a variety of polymers such as NR, CR, SBR, SBS, SIS, EVA, etc. in any proportion.
[0044] In terms of application, 138 resin is widely used in adhesive industry, paint and coating industry, ink industry and electronic chemical industry, etc. In the adhesive industry, it can be used to manufacture hot melt pressure-sensitive adhesives, solvent pressure-sensitive adhesives and hot melt adhesives, such as sanitary napkin adhesives, label adhesives, tape adhesives, etc. In the coating industry, 138 resin can be used to manufacture varnishes and nitro lacquers to improve the adhesion and glossiness of the paint film. In addition, it can also be used as a tackifier or linker for inks to improve the adhesion and printing effect of inks. In the plastics industry, 138 resin can be used as a plasticizer and stabilizer for plastics to improve the flexibility, impact resistance and heat resistance of plastics. Therefore, 138 resin has been widely used in the industrial field due to its unique chemical and physical properties.
[0045] Terpene resin is a thermoplastic resin processed from natural turpentine, with many excellent properties. It is usually a light yellow viscous liquid or a transparent brittle solid, non-toxic, odorless, radiation-resistant, anti-crystallization, relatively stable to oxygen, heat, and light; has good compatibility with various synthetic substances; is resistant to dilute acids and dilute alkalis; has strong viscosity, strong electrical insulation, and is insoluble in water and ethanol. Terpene resin has stable chemical properties, is heat-resistant and light-resistant, is difficult to oxidize in the air, does not crystallize, and has good insulation.
[0046] In terms of application, terpene resin is widely used in adhesives, adhesives, double-sided tapes, solvent-based glues, book bindings, packaging, tapes, olefin tapes, kraft paper tapes, tape labels, woodworking glues, pressure-sensitive adhesives, hot melt adhesives, sealants, paints and inks due to its excellent tackifying properties. It is also a modifier for hot melt materials. When used with C5 petroleum resin, it can solve the water-based (water seepage) phenomenon when it is used alone. It has excellent heat resistance, weather resistance, aging resistance, and tackifying effect in SBS hot melt adhesives. In addition, terpene resin emulsions are often used as sizing agents for fabrics, showing its diverse uses in industry.
[0047] The role of filler aggregate in sealant is mainly reflected in enhancing the physical properties and chemical stability of sealant. Filler aggregate can improve the hardness and compressive strength of sealant, so that the sealant forms a stronger sealing layer after curing, effectively preventing the invasion of external environment such as moisture, dust, etc. In addition, filler aggregate can also improve the thermal stability and chemical corrosion resistance of sealant, so that it can maintain a good sealing effect under different environmental conditions. At the same time, the addition of filler aggregate can also adjust the fluidity and thixotropy of sealant, making it easier to construct and shape, and improving construction efficiency. In general, filler aggregate plays a multiple role in sealant to enhance, stabilize and improve construction performance.
[0048] In some embodiments, the filler aggregate includes nano calcium carbonate and ultrafine wollastonite powder. The application of nano calcium carbonate in sealants is mainly reflected in its use as a reinforcing filler, which can significantly improve the mechanical properties of sealants, such as adhesion, tensile strength and hardness, while improving processing performance and thixotropic properties. In addition, nano calcium carbonate can also reduce production costs, and optimize the construction performance and stability of sealants through its particle size, specific surface area and surface treatment characteristics, making it a key functional filler in the sealant industry.
[0049] Ultrafine wollastonite powder is a powder obtained through special processing, with extremely fine particle size and large surface area. With its unique physical and chemical properties, it shows excellent performance in many fields. The main uses of this powder include coatings, rubber, metallurgy and other industries. In the field of coatings, ultrafine wollastonite powder can provide good appearance, wear resistance, chemical corrosion resistance, stripping resistance and heat resistance, etc. It is the most used and widely used high-quality filler in modern coatings.
[0050] The role of ultrafine wollastonite powder in the rubber industry is mainly reflected in improving the appearance of rubber products, enhancing their impact resistance, improving the elasticity of rubber products, reducing the impact of temperature changes, enhancing the durability and endurance of rubber products, and increasing the hardness of rubber, so that it can withstand greater pressure while maintaining elastic properties. In the field of metallurgy, wollastonite powder has good solidification properties for metal materials, which can avoid the occurrence of mold release during metal melting, reduce material size deformation, make the surface neat and flat, and improve precision. In addition, ultrafine wollastonite powder also has excellent antioxidant properties and has good performance in many industrial fields.
[0051] In some embodiments, the rust and corrosion inhibitor of the present application is a mixture of modified aluminum tripolyphosphate and zinc oxide. Modified aluminum tripolyphosphate is a pigment based on aluminum tripolyphosphate and modified by adding other chemical substances. It has excellent anti-rust properties and good chemical stability. Modified aluminum tripolyphosphate is widely used in various coatings, including thick paste coatings, powder coatings, organic titanium anti-corrosion coatings, rust-bearing coatings, asphalt paints, zinc-rich primers, fire-retardant coatings and heat-resistant coatings. It can replace traditional toxic anti-rust pigments such as red lead, zinc chrome yellow, etc., and is widely used in primers and primer-top integrated coatings.
[0052] Through modification, the chemical stability and anti-rust performance of aluminum tripolyphosphate can be improved, so that it can show better anti-corrosion effect in various complex environments. In addition, as a pollution-free white anti-rust pigment, modified aluminum tripolyphosphate does not contain harmful heavy metal elements such as lead and chromium, which meets environmental protection requirements.
[0053] Aluminum tripolyphosphate can be modified by alkaline oxides to improve its anti-corrosion performance. The alkaline oxides can be zinc oxide, calcium oxide, magnesium oxide, etc. The specific operation method is to mix aluminum tripolyphosphate with alkaline oxides to form a suspension, react for a period of time, and dry to obtain modified aluminum tripolyphosphate.
[0054] Zinc oxide has an anti-mildew effect and can inhibit the growth of microorganisms and fungi. Zinc oxide added to the sealant material can form a dense zinc-titanium compound, reduce the speed of further penetration of corrosive media, and play an anti-rust role.
[0055] The present invention mixes modified aluminum tripolyphosphate with zinc oxide powder to prepare an anti-rust and anti-corrosion agent, thereby improving the anti-corrosion and waterproof performance of the sealant and extending the service life of the fastener.
[0056] In some preferred embodiments, the addition amount of modified aluminum tripolyphosphate and zinc oxide powder is (2.5-1):1. In a more preferred embodiment, the mass ratio of modified aluminum tripolyphosphate to zinc oxide powder is 1:1.
[0057] The present application also provides a method for preparing an anti-corrosion and waterproof sealant for nuts, which comprises gradually heating up a reaction container, adding polyisobutylene and a softener and continuously stirring to dissolve, heating to 120°C and sequentially adding a thermoplastic elastomer, an anti-corrosion and rust inhibitor, and a thickener, and adding the next reactant after the previous reactant is completely dissolved, heating the reaction container to 150°C and adding the thickener, stirring until the thickener is completely dissolved, and then adding a filling aggregate to obtain an anti-corrosion and waterproof sealant for nuts of the present application.
[0058] The present application also provides an application method of the nut anti-corrosion and waterproof sealant. After the nut anti-corrosion and waterproof sealant is released and solidified, a dispensing machine is used to heat and melt it, and the circular shell is placed on the operating table and filled with glue. After the sealant solidifies, a release paper is pasted on it, and the finished product is completed. Figure 1 shown.
[0059] The nut anti-corrosion and waterproof sealant of the present application is in a semi-solidified state, and the involvement of moisture and corrosive substances has been reduced during the preparation process. In the sealing of actual fasteners, it can reduce the curing time and enhance the anti-corrosion and waterproof effects.
[0060] The present application provides a sealing member for nuts, comprising an open shell, the interior of which is suitable for containing the above-mentioned nut anti-corrosion and waterproof sealant, and release paper is suitable for sticking on the nut anti-corrosion and waterproof sealant for protection.
[0061] In the nut seal of the present application, the Mooney viscosity of the nut anticorrosion and waterproof sealant contained in the shell is in the range of 3 to 4. Within the suitable Mooney viscosity range, the nut anticorrosion and waterproof sealant of the present application is in a semi-solidified state. When using the nut seal of the present application, tear off the release paper, face the open end of the shell toward the nut to be sealed, and press hard so that the exposed nut is covered with the sealant. Figure 2 shown.
[0062] The nut seal of the present application realizes the sealing covering of the nut very conveniently and quickly. It can be used immediately without waiting, and can be transported as a solid during transportation, which is environmentally friendly and reduces costs, and has good practical application significance.
[0063] Example 1
[0064] The present application provides a method for preparing a nut anti-corrosion and waterproof sealant as follows:
[0065] The temperature of the reaction container is increased, and 40 parts by mass of polyisobutylene and 25 parts by mass of softener are added at the same time, and stirring is continued until dissolved. The temperature of the reaction container is increased to 120°C, and 10 parts by mass of thermoplastic elastomer is added. After the thermoplastic elastomer is completely dissolved, a rust preventive and corrosion inhibitor is added. The amount of the rust preventive and corrosion inhibitor added is 3% of the total mass. After the rust preventive and corrosion inhibitor is completely dissolved, 70 parts by mass of viscosity enhancer is added. Subsequently, the temperature of the reaction container is increased to 150°C, 70 parts by mass of viscosity enhancer is added, and stirring is performed until completely dissolved. 85 parts by mass of filling aggregate is added, and the filling aggregate is stirred until completely dissolved to obtain a nut anticorrosive and waterproof sealant of the present application.
[0066] Specifically, the polyisobutylene is South Korea's Daelim PB950 and PB1300, the softener is Karamay Petrochemical KN4006 and KN4010, the thermoplastic elastomer is a mixture of 5 parts by mass of linear SEBS and 5 parts by mass of linear SEPS, the rust and corrosion inhibitor is a mixture of modified aluminum tripolyphosphate and zinc oxide in a mass ratio of 1:1, the viscosity enhancer is 138 resin, and the filling aggregate is nano calcium carbonate and ultrafine wollastonite powder.
[0067] Example 2
[0068] The mass ratio of modified aluminum tripolyphosphate and zinc oxide in the rust and corrosion inhibitor was adjusted to 5:2, and the other preparation steps were consistent with the preparation steps in Example 1.
[0069] Comparative Example 1
[0070] 3% by mass of modified aluminum tripolyphosphate was added to replace the rust and corrosion inhibitor, and the other preparation steps were consistent with those in Example 1.
[0071] Comparative Example 2
[0072] 3% by mass of zinc oxide was added to replace the rust and corrosion inhibitor, and the other preparation steps were consistent with those in Example 1.
[0073] Comparative Example 3
[0074] No softener was added during the preparation, and the other preparation steps were consistent with the preparation steps in Example 1, so as to prepare the sealant of Comparative Example 3.
[0075] Comparative Example 4
[0076] No filler aggregate is added during the preparation, and the other preparation steps are consistent with the preparation steps in Example 1, so as to prepare the sealant of Comparative Example 3.
[0077] Performance Testing
[0078] 1. Mooney viscosity ML (1+4) 50°C: The sealants of each embodiment and each comparative example were tested according to the test method of GB / T132.1-2016;
[0079] 2. Salt spray test: The nuts are sealed with the sealant of this application and fixed in a salt spray test chamber. The test chamber temperature is set to 35±2°C and the salt solution concentration is 5%±1%. A continuous spray test is performed for 72 hours. After the test, the sample is taken out and the surface is rinsed with clean water. The corrosion condition of the sample surface is observed and recorded to see whether there are corrosion spots and the size of the corrosion area.
[0080] The results of the above performance tests are recorded in Table 1.
[0081] Table 1 Performance test results of each embodiment and each comparative example project Mooney viscosity Salt spray test Example 1 3.5 excellent Example 2 3.8 excellent Comparative Example 1 2.8 good Comparative Example 2 4.3 good Comparative Example 3 6.7 good Comparative Example 4 2.2 good
[0082] The nut anti-corrosion and waterproof sealant of the present application is prepared by compounding the raw material formula to obtain a sealant with a Mooney viscosity range of 3 to 4. It can be easily used to provide anti-corrosion and waterproof protection for nuts and extend the service life of fasteners.
[0083] In the results of the salt spray test, the nut anti-corrosion and waterproof sealant of the present application provides better anti-corrosion performance, effectively reduces the corrosion area, and has a better anti-corrosion effect.
[0084] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.
Claims
1. A nut anti-corrosion and waterproof sealant, characterized in that: The raw materials for preparation include the following components: polyisobutylene, thermoplastic elastomer, softener, tackifier, filling aggregate and antirust and corrosion inhibitor, wherein the antirust and corrosion inhibitor is a mixture of modified aluminum tripolyphosphate and zinc oxide.
2. The nut anticorrosion and waterproof sealant according to claim 1, characterized in that: The modified aluminum tripolyphosphate and the zinc oxide are mixed in a mass ratio of (2.5-1):1 to obtain the rust and corrosion inhibitor.
3. The nut anticorrosion and waterproof sealant according to claim 2, characterized in that: The modified aluminum tripolyphosphate and the zinc oxide are mixed in a mass ratio of 1:1 to obtain the rust and corrosion inhibitor.
4. The nut anticorrosion and waterproof sealant according to claim 1, characterized in that: The added amount of the anti-rust and anti-corrosion agent is 3% to 7% of the total mass.
5. The nut anticorrosion and waterproof sealant according to claim 4, characterized in that: The raw materials for preparation include the following components: 20 to 60 parts by weight of the polyisobutylene, 10 to 40 parts by weight of the softener, 10 to 20 parts by weight of the thermoplastic elastomer, 50 to 80 parts by weight of the tackifier, and 60 to 100 parts by weight of the filling aggregate. The amount of the rust and corrosion inhibitor is 3% to 7% of the total mass.
6. The nut anticorrosion and waterproof sealant according to claim 5, characterized in that: The raw materials for preparation include the following components: 40 parts by mass of the polyisobutylene, 25 parts by mass of the softener, 10 parts by mass of the thermoplastic elastomer, 70 parts by mass of the tackifier, 85 parts by mass of the filling aggregate, and the amount of the rust and corrosion inhibitor is 3% of the total mass.
7. The nut anticorrosion and waterproof sealant according to claim 1, characterized in that: The filling aggregate is nano calcium carbonate and / or ultrafine wollastonite powder, the tackifier is any one or more combinations of 138 resin, terpene resin, carbon nine or carbon five, the softener is cycloalkane, and the thermoplastic elastomer is a mixture of modified linear thermoplastic styrene butadiene rubber SEBS and linear SEPS.
8. The nut anticorrosion and waterproof sealant according to any one of claims 1 to 7, characterized in that: The Mooney viscosity range is 3 to 4.
9. The method for preparing the nut anticorrosion and waterproof sealant according to any one of claims 1 to 8, characterized in that: Heat the reaction container and add the polyisobutylene and the softener at the same time, and continue stirring until dissolved. Heat the reaction container to 100-120° C. and then add the thermoplastic elastomer, the anticorrosion and rust inhibitor and the adhesive in sequence. After each of the above reactants is dissolved, add the next reactant. Finally, heat the reaction container to 130-150° C. and add the tackifier. After the tackifier is dissolved, add the filling aggregate to obtain the nut anticorrosion and waterproof sealant.
10. A sealing member, characterized in that: It comprises an open shell, wherein the shell contains the nut anticorrosion and waterproof sealant as claimed in any one of claims 1 to 8, or contains the nut anticorrosion and waterproof sealant prepared by the preparation method as claimed in claim 9.